THE METHODOLOGICAL APPROACHES TO THE REFORM OF THE SYSTEM HEALTH CARE IN UKRAINE - Орищин, Тетяна Михайлівна; Орищин, Олексій Миколайович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Development of medical insurance is one of the most urgent and perspective direction of funding of public health care programs. The purpose of transformations to the existent system of health care is market of medical services creation at the observance of principle of satisfaction of necessities of population in medicare. In reformation of the system of the medical providing in Ukraine is restructuring of existent network of establishments of health care and rational prognostication of quantity of medical personnel in accordance with the volume of the planned work and necessities of population in medicare.